Optimization of Ultrasound-Assisted Extraction (UAE) Parameters of Clitoria ternatea L. Using Response Surface Methodology: Effects on Phytochemical Content and UV-Protective Activity - Firdausia, Rizqa Salsabila; Rusydan, Azka Muhammad; Rikhaturhohmah, Rikhaturhohmah; Lastanti, Eka Sepfiya Harya; Azizah, Nayla Nur Alfina; Dhanty, Tyas Eka Rama; Sari, Kurnia Rahayu Purnomo (Journal of Fundamental and Applied Pharmaceutical Science, 2026)
Solar radiation includes ultraviolet (UV) rays that can induce adverse effects on the skin due to increasing environmental exposure. Sunscreen application is an effective approach to prevent UV-related skin damage, and natural products rich in phenolic and flavonoid compounds have gained attention as alternative photoprotective agents. This study aimed to determine the optimal UAE conditions for Clitoria ternatea flower to achieve maximum secondary metabolite content and UV-protective activity, evaluated through total phenolic content (TPC), total flavonoid content (TFC), Sun Protection Factor (SPF), percentage of erythema transmission (%Te), and pigmentation transmission (%Tp). Optimization was performed using Response Surface Methodology (RSM) with a Box–Behnken Design generated by Design-Expert® software version 13, involving three independent variables and 15 experimental runs. Phytochemical screening confirmed that all extract batches contained phenolic and flavonoid compounds. RSM analysis successfully identified the optimal extraction parameters at a solid-to-solvent ratio of 14.51, an ethanol–water solvent ratio of 100:0, and an extraction time of 60 minutes. Under these conditions, the predicted responses were 38.37 mg GAE/g extract for TPC, 44.05 mg QE/g extract for TFC, an SPF value of 17.31, %Te of 1.40%, and %Tp of 2.02%. These findings demonstrate that optimized UAE enhances the recovery of bioactive compounds and improves the UV-protective potential of Clitoria ternatea flower extract, supporting its application as a natural sunscreen agent.